2014
DOI: 10.1111/epi.12628
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β associations with posttraumatic epilepsy development: A genetics and biomarker cohort study

Abstract: Objective Post-traumatic epilepsy (PTE) is a significant complication following traumatic brain injury (TBI), yet the role of genetic variation in modulating PTE onset is unclear. We hypothesized that TBI-induced inflammation likely contributes to seizure development. We assessed whether genetic variation in the IL-1β gene, Il-1β levels in cerebral spinal fluid (CSF) and serum, and CSF/serum IL-1β ratios would predict PTE development post-TBI. Methods We investigated PTE development in 256 Caucasian adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 53 publications
(47 reference statements)
3
68
0
1
Order By: Relevance
“…Many studies have shown that genetic variation is associated with outcomes and conditions following TBI (Hoh et al, 2010;Weaver et al, 2012;Wagner et al, 2012;Garringer et al, 2013;Diamond et al, 2014;Failla et al, 2014). Of note, an IL-6 polymorphism (À174 G/C) has been reported as associated with mortality after severe TBI (Dalla Libera et al, 2011) and the development of Alzheimer's disease in non-TBI populations (Qi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that genetic variation is associated with outcomes and conditions following TBI (Hoh et al, 2010;Weaver et al, 2012;Wagner et al, 2012;Garringer et al, 2013;Diamond et al, 2014;Failla et al, 2014). Of note, an IL-6 polymorphism (À174 G/C) has been reported as associated with mortality after severe TBI (Dalla Libera et al, 2011) and the development of Alzheimer's disease in non-TBI populations (Qi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared to the existent traumatic brain injury model [54, 55], parenchymal brain calcified cysticerci have the advantage of being much more homogeneous and predictable in their structure and evolution than are traumatic brain lesions. Knowledge provided from these suggested cohort studies might also allow the development of novel interventions to prevent chronic epilepsy in NCC and perhaps in other forms of acquired epilepsy.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Studies have characterized certain candidate cytokines, chemokines, cell-surface markers, and microglia as elevated early after injury compared to uninjured controls (Woodcock and Morganti-Kossmann, 2013). Contemporary concepts contend that controlled inflammation is necessary to clear debris and damaged cells early following TBI, while sustained elevations of inflammatory markers, such as IL-1β, TNFα, and IL-6, are deleterious if not physiologically regulated and can lead to an increased risk of depression (Juengst et al , 2014), epilepsy (Diamond et al , 2014), cognitive deficits (Clausen et al , 2009, 2011) and poor global outcomes (Kumar et al , 2014). …”
Section: Introductionmentioning
confidence: 99%